Electrochemical meta-C-H sulfonylation of pyridines with nucleophilic sulfinates - Qin, Shi; Yang, Mingkai; Xu, Mingyao; Peng, Zhi-Huan; Cai, Jiating; Wang, Shengdong; Gao, Hui; Zhou, Zhi; Hashmi, A. Stephen K.; Yi, Wei; Zeng, Zhongyi (Nature Communications, 2024)
Considering the indispensable significance and utilities of meta-substituted pyridines in medicinal, chemical as well as materials science, a direct meta-selective C-H functionalization of pyridines is of paramount importance, but such reactions remain limited and highly challenging. In general, established methods for meta C-H functionalization of pyridines rely on the utilization of tailored electrophilic reagents to realize the intrinsic polarity match. Herein, we report a complementary electrochemical methodology; diverse nucleophilic sulfinates allow meta-sulfonylation of pyridines through a redox-neutral dearomatization-rearomatization strategy by a tandem dearomative cycloaddition/hydrogen-evolution electrooxidative C-H sulfonation of the resulting oxazino-pyridines/acid-promoted rearomatization sequence. Besides, several salient features, including exclusive regiocontrol, remarkable substrate/functional group compatibility, scale-up potential, and facile late-stage modification, have been demonstrated, which further contributes to the practicality and adaptability of this approach.
Online veröffentlicht: 28. August 2024
Gesehen am 15.10.2025